2020
DOI: 10.1111/adb.12971
|View full text |Cite
|
Sign up to set email alerts
|

Stress induces reinstatement of extinguished cocaine conditioned place preference by a sequential signaling via neuropeptide S, orexin, and endocannabinoid

Abstract: Neurons containing neuropeptide S (NPS) and orexins are activated during stress. Previously, we reported that orexins released during stress, via orexin OX1 receptors (OX1Rs), contribute to the reinstatement of cocaine seeking through endocannabinoid/CB1 receptor (CB1R)‐mediated dopaminergic disinhibition in the ventral tegmental area (VTA). Here, we further demonstrated that NPS released during stress is an up‐stream activator of this orexin‐endocannabinoid cascade in the VTA, leading to the reinstatement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Indeed, we reported that NPS increased cFos expression in the hypothalamic Hcrt1/Ox-A cells [ 19 , 20 ], and intra-LH injections of NPS (0.5 nmol) markedly increased the cue-induced reinstatement of cocaine seeking [ 20 ], an effect that was abolished by pretreatment with the selective Ox-1 receptor antagonist SB-334867 (10mg/kg, i.p.). In agreement with these data, more recently, Chou and collaborators [ 102 ] demonstrated that i.c.v. infusions of NPS (1 nmol) augmented cFos-containing orexin neurons in the LH and the Ox-A level in the VTA [ 102 ].…”
Section: Role Of Nps In Cocaine Seekingsupporting
confidence: 69%
See 1 more Smart Citation
“…Indeed, we reported that NPS increased cFos expression in the hypothalamic Hcrt1/Ox-A cells [ 19 , 20 ], and intra-LH injections of NPS (0.5 nmol) markedly increased the cue-induced reinstatement of cocaine seeking [ 20 ], an effect that was abolished by pretreatment with the selective Ox-1 receptor antagonist SB-334867 (10mg/kg, i.p.). In agreement with these data, more recently, Chou and collaborators [ 102 ] demonstrated that i.c.v. infusions of NPS (1 nmol) augmented cFos-containing orexin neurons in the LH and the Ox-A level in the VTA [ 102 ].…”
Section: Role Of Nps In Cocaine Seekingsupporting
confidence: 69%
“…In agreement with these data, more recently, Chou and collaborators [ 102 ] demonstrated that i.c.v. infusions of NPS (1 nmol) augmented cFos-containing orexin neurons in the LH and the Ox-A level in the VTA [ 102 ]. This latter effect was prevented by the NPS receptor antagonist SHA 68 (50 mg/kg, i.p.…”
Section: Role Of Nps In Cocaine Seekingsupporting
confidence: 69%
“…Such findings suggest that the reinstatement of cocaine-induced CPP by NPS likely involves NPS-cannabinoid-orexin cross-talks in brain areas involved in the behavioural motivation circuit [ 63 ]. This was further confirmed at the molecular level by the observation that NPS increased the activation of orexinergic neurons in the LH as well as enhanced orexin A levels in the ventral tegmental area (VTA) [ 62 ].…”
Section: Role Of the Nps/npsr1 System In Addiction-like Behavioursmentioning
confidence: 97%
“…In one study, NPS significantly reduced the expression of morphine-induced CPP but it did not affect the hyper-locomotor effects of morphine [ 61 ], suggesting distinct mechanisms for NPS modulation of the reinforcing and locomotor properties of this drug. In another study, NPS did not affect cocaine-induced CPP expression and extinction [ 62 ]. However, NPS increased the reinstatement of cocaine-induced CPP, which was blocked by the NPSR1 antagonist SHA68, an orexin receptor 1 (ORX1) antagonist (e.g., SB334867) or a cannabinoid receptor 1 (CB1R) antagonist (e.g., AM251).…”
Section: Role Of the Nps/npsr1 System In Addiction-like Behavioursmentioning
confidence: 99%
See 1 more Smart Citation